2016
DOI: 10.3109/14767058.2016.1140141
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transcutaneous bilirubin measured by the BiliCare device in late preterm and term neonates

Abstract: The BiliCare(TM) demonstrated good performance with positive bias for the screening of jaundice in healthy late preterm or term infants. However, if adopted, proper cut-off levels should be chosen because of sub-optimal device precision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…This study demonstrated a stronger correlation in the Caucasian group compared to the non‐Caucasian group. These findings are consistent with other studies where the correlation between TcB and SBR in non‐Caucasian or darker‐skinned infants is lower than that of Caucasian or lighter‐skinned infants . The trend in agreement is also consistent with other studies in that TcB devices tend to overestimate the SBR measurements (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study demonstrated a stronger correlation in the Caucasian group compared to the non‐Caucasian group. These findings are consistent with other studies where the correlation between TcB and SBR in non‐Caucasian or darker‐skinned infants is lower than that of Caucasian or lighter‐skinned infants . The trend in agreement is also consistent with other studies in that TcB devices tend to overestimate the SBR measurements (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with other studies where the correlation between TcB and SBR in non-Caucasian or darker-skinned infants is lower than that of Caucasian or lighter-skinned infants. 11,13,[15][16][17][18][19][20] The trend in agreement is also consistent with other studies in that TcB devices tend to overestimate the SBR measurements (i.e. positive bias) in non-Caucasian or darker-skinned infants (including African American, Thai and Asian sub-populations) and are less precise than measurements in Caucasian or lighterskinned infants where the devices tended to underestimate (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two study groups in Italy and Thailand reported the accuracy of BiliCare TcB in 2016; the r between TcB and TB was 0.55 and 0.76, respectively . The mean difference on Bland–Altman plots was +1.87 in the Thailand study .…”
Section: Discussionmentioning
confidence: 95%